ANALISIS SIKAP DAN KEPUTUSAN NASABAH DALAM PENGGUNAAN PRODUK JENIUS-PERBANKAN DIGITAL (Studi pada Forum Komunitas Jenius- Jenius Co.Create) - Putri, Atalya; Kancana, Sauptika; Mulyanto, Indro Herry (Jurnal Paradigma, 2021)
This research was conducted to determine the customer's attitude in the use of Jenius-Digital Banking products and also customer decisions in the use of Jenius-Digital Banking products through Fishbein Multi attribute method.  The population in this study is a member of the Jenius Community Forum - Jenius Co.Create. The determination of the sample count will be determined by a level of confidance of 90% and a margin of error of 10%. The sample determination technique used in this study is based on the Non Probabiliy Sampling method using the Accidental Sampling approach. The results showed that (1) the results of the calculation of the attitude of Jenius-Digital Banking customers with the Fishbein Multi attribute model show attitudes with positive interpretation and can be interpreted that respondents who are Jenius-Digital Banking Customers at the Jenius Community Forum - Jenius Co.Create have a positive attitude towards the attributes of Jenius-Digital Banking products; (2) The decision of Jenius-Digital Banking customer indicated by B≈BI result is positive which can be said that the customer will take the decision to continue using Jenius-Digital Banking products.